Drivers of smartwatch use and its effect on environmental sustainability: evidence from SEM-ANN approach - Almheiri E.; Al-Emran M.; Al-Sharafi M.A.; Arpaci I. (Emerald Publishing, 2025)
Purpose: The proliferation of smartwatches in the digital age has radically transformed health and fitness management, offering users a multitude of functionalities that extend beyond mere physical activity tracking. While these modern wearables have empowered users with real-time data and personalized health insights, their environmental implications remain relatively unexplored despite a growing emphasis on sustainability. To bridge this gap, this study extends the UTAUT2 model with smartwatch features (mobility and availability) and perceived security to understand the drivers of smartwatch usage and its consequent impact on environmental sustainability. Design/methodology/approach: The proposed theoretical model is evaluated based on data collected from 303 smartwatch users using a hybrid structural equation modeling?artificial neural network (SEM-ANN) approach. Findings: The PLS-SEM results supported smartwatch features? effect on performance and effort expectancy. The results also supported the role of performance expectancy, social influence, price value, habit and perceived security in smartwatch usage. The use of smartwatches was found to influence environmental sustainability significantly. However, the results did not support the association between effort expectancy, facilitating conditions and hedonic motivation with smartwatch use. The ANN results further complement these outcomes by showing that habit with a normalized importance of 100% is the most significant factor influencing smartwatch use. Originality/value: Theoretically, this research broadens the UTAUT2 by introducing smartwatch features as external variables and environmental sustainability as a new outcome of technology use. On a practical level, the study offers insights for various stakeholders interested in smartwatch use and their environmental implications. ? 2024, Emerald Publishing Limited.